2004
DOI: 10.1161/01.hyp.0000115924.94236.91
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Mediates Benefits of Angiotensin II Type 2 Receptor Overexpression During Post-Infarct Remodeling

Abstract: Abstract-We hypothesized that nitric oxide (NO) mediates the benefits of cardiac angiotensin II type 2 (AT 2 -R) overexpression during postmyocardial infarction (post-MI) remodeling. Eleven wild-type (WT) C57BL/6 mice and 28 transgenic (TG) mice with AT 2 -R overexpression were studied by cardiac magnetic resonance imaging (CMR) at baseline and days 1 and 28 post-MI induced by left anterior descending artery occlusion and reperfusion. Sixteen TG mice were treated from day 1 through 28 post-MI with the NO synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…This group of investigators has recently extended this study to demonstrate that the cardiac NO pathway is largely, if not exclusively, responsible for the beneficial effects of AT 2 receptor expression. 35 NOS inhibitor L-NAME was able to abrogate virtually all of the protective actions of cardiac AT 2 receptor overexpression after MI LV remodeling. 35 Beneficial effects of cardiac-specific AT 2 receptor overexpression included reduced LV wall thickening, decreased end-diastolicand end-systolic volume indices, and increased ejection fraction after MI compared with WT mice.…”
Section: Cardioprotective Actions Of At 2 Receptorsmentioning
confidence: 92%
See 1 more Smart Citation
“…This group of investigators has recently extended this study to demonstrate that the cardiac NO pathway is largely, if not exclusively, responsible for the beneficial effects of AT 2 receptor expression. 35 NOS inhibitor L-NAME was able to abrogate virtually all of the protective actions of cardiac AT 2 receptor overexpression after MI LV remodeling. 35 Beneficial effects of cardiac-specific AT 2 receptor overexpression included reduced LV wall thickening, decreased end-diastolicand end-systolic volume indices, and increased ejection fraction after MI compared with WT mice.…”
Section: Cardioprotective Actions Of At 2 Receptorsmentioning
confidence: 92%
“…35 NOS inhibitor L-NAME was able to abrogate virtually all of the protective actions of cardiac AT 2 receptor overexpression after MI LV remodeling. 35 Beneficial effects of cardiac-specific AT 2 receptor overexpression included reduced LV wall thickening, decreased end-diastolicand end-systolic volume indices, and increased ejection fraction after MI compared with WT mice. These results are for the most part consonant with the work of Xu et al, 36 who demonstrated that the cardioprotective effects of AT 1 receptor activation are mediated by the AT 2 receptor, even though the AT 2 receptor may not play a role in the regulation of normal (basal) cardiac function.…”
Section: Cardioprotective Actions Of At 2 Receptorsmentioning
confidence: 92%
“…The importance of elevated ANG II levels in cardiac disease is becoming increasingly clear, and studies have shown evidence for negative outcomes associated with increased AT 1 receptor activation (14,21). Conversely, increased activation of AT 2 receptors is associated with cardioprotection (9,10,25). While cardiomyoctes express AT 1 and AT 2 receptors, most of the functional changes (electrical and mechanical) induced by ANG II exposure to the heart in vivo are mediated indirectly via induced alterations in autonomic efferent function (15,20).…”
Section: R1396 Adrenergic Muscarinic and Ang II Modulation Of Intramentioning
confidence: 99%
“…Some of the beneficial effects of AT 2 R are mediated by bradykinin/ nitric oxide (NO) (5,10), and overexpression of AT 2 R in the vasculature reportedly stimulated the kinin system, causing dilatation (31). Likewise cardiac AT 2 R overexpression attenuated fibrosis induced by ANG II or myocardial infarction, apparently acting via a kinin/NO-dependent mechanism (3,7). We have demonstrated that the cardioprotective effects of AT 1 R antagonists are mediated in part by activation of AT 2 R and kinins, since they were diminished in AT 2 R or kinin receptors knock out mice and kinin-deficient rats or by blocking the AT 2 R or kinin receptors (11, 34 -36).…”
mentioning
confidence: 99%